Women's Leadership in Islamic Boarding Schools: A Case Study at Darus Salam Islamic Boarding School Mandigu Hamlet Suco Village Mumbulsari District Jember Regency - Heidiah Waskito Rini; Imron Sadewo; Muhammad Arif Mustaqim (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
The discourse on women's leadership is still very doubtful in the lives of the people of Mandigu Hamlet, Suco Village, Mumbulsari District, Jember Regency. This can be concluded from the public response that is still very strong toward patriarchal culture and the lack of education. This study has two research focuses, first, what is the mindset of the community towards women's leadership in Darus Salam Islamic Boarding School? Second, is the decline in the number of students related to women's leadership at the Darus Salam Islamic Boarding School? In this study, the feminism method is used with a case study approach that clearly describes what has happened in the field. The purpose of this study, first, is to find out the mindset of the community towards women's leadership in Darus Salam Islamic Boarding School. Second, to find out the factors causing the decline in the number of students of the Darus Salam Islamic Boarding School. The results of this study indicate, firstly, that women's leadership is still not accepted by the surrounding community due to the low level of public education which creates a lack of understanding of the notion of feminism so that people think that women do not deserve to be leaders. Second, several factors that cause the decline in the number of students at Darus Salam Islamic Boarding School are the young age of the next generation of pesantren, there is no pesantren institutional structure, no formal school, and the large number of students who marry young.